Strategi Periklanan Online Shop Garasi Barokah di Media Sosial Instagram - Fadilah, Jusuf (Jurnal Komunikasi, 2019)
Abstract - This study discusses the online shop advertising strategy of Garasi Barokah on social media Instagram. The research method used is qualitative research with the format of field research. The data source in this study consists of two data sets, namely field data and written data. The results showed that the advertising strategy in the diecast manager's perspective, namely the selection of social media Instagram as a means of advertising communication because of the advantages of its social system, namely the Comment and DM features (Direct Message) where the system creates a personal interaction and communication space for business people to exchange messages intensive between traders and traders with buyers. Three aspects in presenting online shop advertising strategies Garasi Barokah on social media Instagram, First, the visual aspect of presenting photos of products is original diecast. Second, the communication aspect, namely the ad text that contains messages about diecast product specifications or specifications, the advantages of diecast products, the price of diecast products, where advertising sentences are made more persuasive which aims to influence consumers. Third, the interactive aspect seeks the service of the purchase or transaction process, contact number and address of the buyer that allows direct interaction between the merchant and the buyer, commonly called Cash On Delivery (COD). The inhibiting factors for the product advertising process are diecast, which is related to incompleteness of identity or found false accounts that are misused by certain individuals. The conclusion of this study recommends that the online shop manager of Garasi Barokah should implement strict rules regarding the identity of buyers (consumers), more effective use of the latest features from Instagram, and implement advertising communication strategies across other social media such as Facebook, Line, Whatsapp and Twitter accounts.Keywords: Advertising Strategy, Garasi Barokah, Instagram